PENGARUH PENGGUNAAN LAGU DAN GERAKAN TERHADAP PENINGKATAN KOSAKATA ANAK USIA DINI DI PAUD AL-FATH, KABUPATEN ACEH SINGKIL - Nuryatin, Nuryatin; Sarlina, Sarlina (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2005)
This study aims to analyze the effect of using songs and movements on increasing the vocabulary of early childhood at PAUD AL-FATH, Aceh Singkil Regency. The method used in this study is a quantitative method with a quasi-experimental design. The research sample consisted of 30 children aged 4-5 years, which were divided into an experimental group and a control group. The experimental group was taught using songs and movements, while the control group used conventional methods. The results showed that the children in the experimental group experienced a significant improvement in vocabulary mastery compared to the control group. Thus, songs and movements can be used as an effective strategy in increasing the vocabulary of young children.